Crystal chemistry of natural layered double hydroxides. 5. Single-crystal structure refinement of hydrotalcite, [Mg6Al2(OH)16](CO3)(H2O)4. (25th July 2018) - Zhitova, Elena S.; Krivovichev, Sergey V.; Pekov, Igor; Greenwell, H. Christopher
Abstract: Hydrotalcite, ideally [Mg6 Al2 (OH)16 ](CO3 )(H2 O)4, was studied in samples from Dypingdal, Snarum, Norway (3 R and 2 H ), Zelentsovskaya pit (2 H ) and Praskovie–Evgenievskaya pit (2 H ) (both Southern Urals, Russia), Talnakh, Siberia, Russia (3 R ), Khibiny, Kola, Russia (3 R ), and St. Lawrence, New York, USA (3 R and 2 H ). Two polytypes, 3 R and 2 H (both 'classical'), were confirmed on the basis of single-crystal and powder X-ray diffraction data. Their chemical composition was studied by electron-microprobe analysis, infrared spectroscopy, differential scanning calorimetry, and thermogravimetric analysis. The crystal structure of hydrotalcite-3 R was solved by direct methods in the space group R $ {\bar 3} $ m on three crystals (two data collections at 290 K and one at 120 K). The unit-cell parameters are as follows (290/290/120 K): a = 3.0728(9)/3.0626(3)/3.0617(4), c = 23.326(9)/23.313(3)/23.203(3) Å and V = 190.7(1)/189.37(4)/188.36(4) Å 3 . The crystal structures were refined on the basis of 304/150/101 reflections to R 1 = 0.075/0.041/0.038. Hydrotalcite-2 H crystallises in the P 63 / mmc space group; unit-cell parameters for two crystals are (data collection at 290 K and 93 K): a = 3.046(1)/3.0521(9), c = 15.447(6)/15.439(4) Å, V = 124.39(8)/124.55(8) Å 3 . The crystal structures were refined on the basis of 160/142 reflections to R 1 = 0.077/0.059. This paper reports the first single-crystal structure data on hydrotalcite. Hydrotalcite distribution in Nature, diagnostic features, polytypism, interlayer topology and localisation of M 2+ – M 3+ cations within metal hydroxide layers are discussed.